The Effect of Brand Image, Product Features, and Social Influence on Buying Interest toward Realme Smartphone Products in Padang City - Nopriandi Nopriandi; Verinita Verinita (Enrichment : Journal of Management, 2021)
This study aims to analyze the influence of brand image variables, product features and social influence on buying interest in Realme Smartphone products in the city of Padang. The scope of this research is on Smartphone respondents in the city of Padang. This research is a quantitative approach using a questionnaire. The sample in this study involved 100 respondents in Padang city and this sample was limited to Android Smartphone respondents. Non-probability sampling is applied in this research by using purposive sampling. Multiple linear regression is used in technique of data analysis through the help of IBM SPSS Statistics 22. The results of this research are the variable brand image on purchase intention have a positive and significant effect and the variable product features on purchase intention have a positive and insignificant effect, in social influence, variable on purchase intention has a positive effect and significant. Based on the results of data processing, it is also found that the variable brand image and social influence are variables that have a big impact on purchase intention in Realme Smartphone products. The better the brand image and social influence, the more buying interest will be in Realme Smartphone products in Padang City.